2011
DOI: 10.1039/c1an15193b
|View full text |Cite
|
Sign up to set email alerts
|

Wearable electrochemical sensors for in situ analysis in marine environments

Abstract: The development of wearable screen-printed electrochemical sensors on underwater garments comprised of the synthetic rubber neoprene is reported. These wearable sensors are able to determine the presence of environmental pollutants and security threats in marine environments. Owing to its unique elastic and superhydrophobic morphology, neoprene is an attractive substrate for thick-film electrochemical sensors for aquatic environments and offers high-resolution printing with no apparent defects. The neoprene-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 22 publications
0
79
0
Order By: Relevance
“…An interesting device based on gold-films deposited on graphite electrodes screen-printed on neoprene has been developed by Malzahn et al [81]. This wearable sensor is able to determine the presence of copper in marine environments.…”
Section: Gold-coated Spesmentioning
confidence: 99%
“…An interesting device based on gold-films deposited on graphite electrodes screen-printed on neoprene has been developed by Malzahn et al [81]. This wearable sensor is able to determine the presence of copper in marine environments.…”
Section: Gold-coated Spesmentioning
confidence: 99%
“…The sensor consisted of Ag working and counter electrodes and a Ag/AgO reference electrode. In the presence of water chloride is liberated from aluminium chlorohydrate which reacts with the Ag working electrode to form free Cl Recently, Malzahn et al [105] have shown the possibility of screen-printing electrochemical sensors onto neoprene diving wet and dry suits. As is illustrated in figure 5 the neoprene material was found to be a suitable substrate to print the working, counter and reference electrodes and could be utilised for the anodic stripping voltammetric determination of Cu ).…”
Section: Platinum Gold and Silver Screen-printed Carbon Electrodesmentioning
confidence: 99%
“…BAN is categorized into three categories: off-body, onbody, and in-body [93,98]. Battery operated systems was another option that was considered where the developed system would be powered by a battery integrated into the system [99,100]. The advantage of using self-powered systems [101][102][103] is that the battery or the power unit of the wireless system does not have to be replaced every time the charging-discharging cycle gets over.…”
Section: Sensor Network For Wearable Flexible Sensorsmentioning
confidence: 99%